Pengaruh variabel ekonomi makro terhadap stabilitas indeks saham syariah Indonesia di bursa efek Indonesia - Masita Bareut (Politeknik Ganesha Medan, 2026)
This study aims to analyze the influence of macroeconomic variables on the Indonesian Sharia Stock Index (ISSI) on the Indonesia Stock Exchange (IDX) with an observation period of 2015-2020. The variables used include inflation, exchange rate, IDR/USD, BI interest rate, Money Supply (M2), world oil prices, Bank Indonesia Sharia Certificates (SBIS), and world gold prices. The data used are secondary quantitative data with a monthly frequency. The analytical method used is descriptive and inferential analysis to test the relationship between macroeconomic variables and ISSI movements. The results show that inflation and BI interest rates have a negative and significant effect, while the money supply and world oil prices have a positive and significant effect. SBIS has a positive but insignificant effect. The coefficient of determination value of 70.5% indicates that these macroeconomic variables are able to explain ISSI fluctuations substantially, while the remaining 29.5% is influenced by other factors outside the research model. These findings emphasize the importance of global and domestic macroeconomic factors in influencing the Islamic capital market. Therefore, investors are advised to pay attention to developments in inflation, exchange rates, oil prices, gold and other monetary indicators, as well as to consider the company's fundamental variables such as profitability, liquidity and growth before making investment decisions in Sharia stocks.